Chaos and "uiut" in Bulgakov's Belaia Gvardiia - Hellebust, Rolf (University of Nottingham, 2013)
The opposition of uiut (the meaning of which is only partially rendered by the English ‘cosiness’) and chaos is identified as a fundamental structural element in Mikhail Bulgakov’s Belaia gvardiia, informing the novel’s construction on a variety of formal and thematic levels. This duality is not so much an objective feature of Bulgakov’s fictional world as an attribute of the fictional consciousnesses through which it is portrayed (those of the Turbin family and their sympathetic narrator). Thus, there are numerous instances of ironic authorial subversions of the uiut/chaos opposition: this is most evident in the case of the novel’s explicit intertexts, the classic works of Russian literature that are for the Turbins the supreme manifestation of the culture of uiut. Yet their wish (ironically fulfilled) to live the life portrayed in these “chocolate books,” from Pushkin’s Kapitanskaia dochka to Bunin’s “Gospodin iz San-Frantsisko,” ignores the focus of these works on chaos and the destruction of uiut. In his use of the literary tradition to convey the fragility/durability of uiut at a time of cultural crisis, Bulgakov echoes the writing of many of his contemporaries. In Pil’njak, Zamjatin, Pasternak and others, one finds notable examples of a similar leitmotif technique (e.g., the stove as a locus of both chaos and uiut) and symbolism (e.g., the house as a microcosm of Russian culture). The subtlety with which Bulgakov juxtaposes the poles of the chaos/uiut opposition through his choice of setting, narrative structure, symbols and leitmotifs proves that Belaia gvardiia is no beginner’s effort, as it has sometimes been regarded, but that it deserves the sort of detailed analysis that would remedy the double eclipse it has historically suffered within Bulgakov’s oeuvre from Master i Margarita and Dni Turbinykh.